Empowering university extension: the role of the internship of the Administration career in different communities in Costa Rica - Miranda-Benavides, Karla (2024)
The aim of this article is to share the experience of the Administration career through internship programs in a regional area of the National University, in different communities in Costa Rica. This document shows the experience in terms of linking with the business sector. To obtain the accurate information in this study, the research team made a compilation of the data corresponding to each practice and it was analyzed based on the evaluations completed by the participating companies in the process. Additionally, the final reports of the course in which the main contributions made by the students in this process were documented. As a result of this work, it is possible to verify the satisfaction level perceived by the participating companies. Likewise, it is possible to demonstrate the results of the professional practices as a strategy of linkage with the business sector in the different regions where they are developed. This article represents relevant information to show the work of higher education institutions in the regions at Costa Rica.